Seroepidemiology of toxoplamosis in renal patients - Nissapatorn, V.; Leong, T.H.; Lee, R.; Init, Ithoi; Ibrahim, J.; Yen, T.S. (2011)
Toxoplasmosis is an important parasitic disease in immunosuppressed patients. This prospective study was conducted to determine the seroprevalence, associated risk factors and the incidence of clinically confirmed toxoplasmosis among renal patients at the University of Malaya Medical Center, Kuala Lumpur, Malaysia. We interviewed 247 renal patients, each of whom answered an epidemiological questionnaire, and collected blood samples for measurement of anti-Toxoplasma IgG and IgM antibodies by ELISA. Overall seroprevalence of latent toxoplasmosis was observed in 126 (51) renal patients. Race (Malays), marital status (married) and primary level of education, were all factors associated with a greater chance of Toxoplasma infection. A case of clinically confirned toxoplasmosis was diagnosed in a renal transplant recipient as a result of immunosuppression. Based on the findings obtained, this preliminary study shows a high prevalence of latent toxoplasmosis in renal patients. Risk factors may have significantly contributed to Toxoplasma acquisition in these patients. We recommend further studies be carried out to monitor for trends in toxoplasmosis among immunosuppressed patients.